Concentration-Dependent Impacts of Microplastics on Soil Nematode Community in Bulk Soils of Maize: Evidence From a Pot Experiment - Yang, Bing; Li, Peng; Entemake, Wulan; Guo, Ziqi; Xue, Sha (Frontiers in Environmental Science, 2022)
Agricultural land soils have become a source and sink for microplastics. Due to the low recycling rate, long durability and small size, microplastics pose a potential risk to soil fauna, which are critical for maintaining a healthy soil. However, whether and how would microplastics affect soil biodiversity and ecological functioning is not well-understood. Soil nematodes are valuable indicators of soil food web. In the present study, the abundance, diversity, community composition, maturity indices, soil food web indices and metabolic footprints of soil nematodes in bulk soils of maize were utilized to indicate the potential impacts of polypropylene (PP) microplastic pollution on soil fauna using a soil-incubation experiment in a climate-controlled chamber with four concentration levels of microplastic pellets ( 0%, 0.5%, 1% and 2%, w/w based on dry weight of soil) added to loess soil collected from the Loess Plateau in China. Soil sampling was conducted at the full ripe stage of maize. Twenty-nine genera of nematodes, including thirteen genera of plant feeding nematodes, seven genera of bacterial-feeding nematodes, five genera of fungal-feeding nematodes and four genera of omnivorous nematodes were recovered from soil samples. Microplastic concentration negatively affected the abundance, diversity (including genus richness, Margalef’s richness, Shannon-Wiener index, and Simpson’s dominance index), Sigma maturity index (∑MI), structural index and metabolic footprints. The abundances of plant parasites, bacterivores, fungivores and omnivores in 2% soils were reduced by 90.16%, 76.06%, 82.35% and 100% respectively in comparison with those of control. The major drivers of soil nematode communities in bulk soils of maize at the depth of 0-20 cm were soil pH, SOC content, C: N and TP content. In conclusion, addition of 200μm-sized PP microplastic pellets negatively affected soil nematode community and associated ecological functioning under greenhouse condition.